Molecular biology of the arterial wall - Schettler, Gotthard (Springer, 1987)
The outstanding contributions to this volume are designed to shed light on some fields of cell biology and cellular pathology, including newly observed phenomena of cell-cell interactions, which might be applicable in studying the pathological process of atherosclerosis. The topics included cover: lipoproteins and lipoprotein receptors; growth factors; endocytosis and exocytosis; ONC Genes and proliferative disease; white blood cells; prostaglandins and leukotrienes; and the biology of smooth muscle and endothelium. The volume provides a complete summary of the most important developments in the field with great impact for arteriosclerosis research
Keywords: Konferenzschrift -- 1986 -- Heidelberg; Zellularpathologie; Pathogenese; Arteriosklerose